White adipose tissue IFN-γ expression and signalling along the progression of rodent cancer cachexia - Yamashita, Alex Shimura; das Neves, Rodrigo Xavier; Rosa-Neto, José Cesar; Lira, Fábio dos Santos [UNESP]; Batista, Miguel Luís; Alcantara, Paulo Sérgio; Otoch, José Pinhata; Seelaender, Marília (My University, 2017)
Cachexia is associated with increased morbidity and mortality in cancer. The White adipose tissue (WAT) synthesizes and releases several pro-inflammatory cytokines that play a role in cancer cachexia-related systemic inflammation. IFN-γ is a pleiotropic cytokine that regulates several immune and metabolic functions. To assess whether IFN-γ signalling in different WAT pads is modified along cancer-cachexia progression, we evaluated IFN-γ receptors expression (IFNGR1 and IFNGR2) and IFN-γ protein expression in a rodent model of cachexia (7, 10, and 14 days after tumour implantation). IFN-γ protein expression was heterogeneously modulated in WAT, with increases in the mesenteric pad and decreased levels in the retroperitoneal depot along cachexia progression. Ifngr1 was up-regulated 7 days after tumour cell injection in mesenteric and epididymal WAT, but the retroperitoneal depot showed reduced Ifngr1 gene expression. Ifngr2 gene expression was increased 7 and 14 days after tumour inoculation in mesenteric WAT. The results provide evidence that changes in IFN-γ expression and signalling may be perceived at stages preceding refractory cachexia, and therefore, might be employed as a means to assess the early stage of the syndrome.
Keywords: Cancer-cachexia; Interferon-γ signalling; White adipose tissue